Cover Feature: Thermodynamically Stable o‐Quinodimethane: Synthesis, Structure, and Reactivity (Chem. Eur. J. 11/2021). Issue 11 (22nd December 2020) - Adachi, Kazuhiko; Hirose, Shunsuke; Ueda, Yasuyuki; Uekusa, Hidehiro; Hamura, Toshiyuki
Abstract : Thermal ring‐opening of cyclobutaphenanthrenes into thermodynamically stable o ‐quinodimethanes is reported in this work. In the cover artwork, the balance of the Lady Justice indicates that energy difference between the energy loss due to dearomatization of the benzene ring in cyclobutaphenanthrene and the strain energy of the four‐membered ring is decisive for ring‐opening. The o ‐quinodimethanes obtained through this strategy can be used as a reactive platform to access novel polycyclic aromatic compounds. More information can be found in the Communication by T. Hamura et al. on page 3665 .